Biodegradable Thermogel as Culture Matrix of Bone Marrow Mesenchymal Stem Cells for Potential Cartilage Tissue Engineering - Zhang, Yan-bo; Ding, Jian-xun; Xu, Wei-guo; Wu, Jie; Chang, Fei; Zhuang, Xiu-li; Chen, Xue-si; Wang, Jin-cheng (Chinese journal of polymer science, 2014)
Poly（lactide-co-glycolide）-poly（ethylene glycol）-poly（lactide-co-glycolide）（PLGA-PEG-PLGA） triblock copolymer was synthesized through the ring-opening polymerization of LA and GA with PEG as macroinitiator and stannous octoate as catalyst. The amphiphilic copolymer self-assembled into micelles in aqueous solutions, and formed hydrogels as the increase of temperature at relatively high concentrations（〉 15 wt%）. The favorable degradability of the hydrogel was confirmed by in vitro and in vivo degradation experiments. The good cellular and tissular compatibilities of the thermogel were demonstrated. The excellent adhesion and proliferation of bone marrow mesenchymal stem cells endowed PLGA-PEGPLGA thermogelling hydrogel with fascinating prospect for cartilage tissue engineering.